Implementation of binary search on website-based traffic data - Najah, Novi Muhimmah Lailatun; Huda, Walidini Syaihul (Institute of Computer Science (IOCS), 2025)
Fast and efficient data retrieval is a fundamental requirement in the development of web-based systems, especially in environments with large volumes of data. The goal of this study is to implement the Binary Search algorithm on the PT Jasamarga Pandaan Tol website to enhance the efficiency of the data retrieval process. System development was carried out using the waterfall method. The Binary Search algorithm was applied to a systematically sorted dataset. Then, the average time required for the search process was measured through testing. After conducting 100 searches on a dataset of 1,000 entries, we found that the average search time was 24.135 milliseconds. This finding indicates that the algorithm operates optimally and efficiently, making it suitable for implementation in large-scale information systems. The efficiency of the search algorithm is crucial to enhancing the system's overall performance.